Agreement of Different Angiography-Derived Modalities With Wire-Based Fractional Flow Reserve Systems and 30 Month Clinical Outcomes in Evaluation of Non-Hemodynamically Significant Obstructive Coronary Artery Disease, a Single Centre Experience - Chow, Han Bing; Chandan, Bhavnani; Ho, Kian Hui; Ting, Tan Chen; Francis, Shu; Koh, Keng Tat; Oon, Yen Yee; Asri, Said; Alan, Fong; Ong, Tiong Kiam (Elsevier, 2023)
Background Coronary physiological is recommended in contemporary guidelines to measure non flow limiting stenosis in patients with stable coronary artery disease (CAD). Application of computational fluid dynamics to derive fractional flow reserve (FFR) eliminates the potential complications associated with hyperaemia and introduction of wires into the coronary arteries. The novel modality has shown consistent accuracy in lesion selection for percutaneous coronary intervention (PCI) and has potential to increase adoption of coronary physiological assessment in Malaysia. Objective To assess the 30-month clinical outcomes of PCI deferral, guided by an angiography based fractional flow reserve (CAFFR) system and the agreement of this application with quantitative flow ratio (QFR) and wired based FFR. The primary end point was a composite of death from any cause, myocardial infarction (MI) or target vessel revascularization (TVR). Methods A prospective, single centre study was conducted from December 2019 to June 2020 involving 69 patients (93 vessels) with angiographic stenosis of 30%-90%. PCI deferral was elected for 29 patients with CAFFR of more than 0.80. Wired FFR was done for comparison at the operator’s discretion. QFR analysis was carried out offline on patients with 2 angiographic views 25 degree apart to compare respective values. Results Amongst the patients who had PCI deferral, 83% were male. The mean age was 59.9 ± 12.6 years old. 12 (41%) patients were diabetic, 18 (62.1%) were hypertensive, 17 (60%) had dyslipidemia and 18 (62%) had a smoking history. The mean LVEF was 53+/-11.4%. 22 (76%) of the patients had a recent acute coronary syndrome. LAD artery was assessed in 16 (52%) vessels. The mean CAFFR, FFR and QFR was 0.80 ± 0.05, 0.89 ± 0.05 and 0.83 ± 0.05 respectively. There were no significant discrepancies between the values with narrow limits of agreement in Bland-Altman plots comparing each modality. There was no statistically significant proportional bias for the Bland Altman plots of CaFFR vs FFR, QFR vs FFR, however there was a significant proportional bias for the Bland-Altman plot for QFR vs CaFFR (linear regression t test: t=2.249, p = 0.031). In general, all three modalities showed good correspondence in significant (<0.80) and non-significant values (>0.80). There were zero procedural complications from CAFFR measurement and similarly for QFR measurements which were conducted offline. At 30 months, all 29 patients were alive. 2 patient (6.8%) met the primary end point (TVR for angina). 89.6% (26) patients remained in CCS class 1 on follow up. Conclusion The 30-month outcome data illustrates the efficacy of PCI deferral utilizing non-wired based techniques that is comparable to the gold standard wired FFR. Future research with a larger sample size and longer follow-up is desired.